Collateral Damage : Exchange Controls and International Trade - Zhang, Zhiwei (IMF Working Papers; Working Paper ;, 2007)
While new conventional wisdom warns that developing countries should be aware of the risks of premature capital account liberalization, the costs of not removing exchange controls have received much less attention. This paper investigates the negative effects of exchange controls on trade. To minimize evasion of controls, countries often intensify inspections at the border and increase documentation requirements. Thus, the cost of conducting trade rises. The paper finds that a one standard-deviation increase in the controls on trade payment has the same negative effect on trade as an increase in tariff by about 14 percentage points. A one standard-deviation increase in the controls on FX transactions reduces trade by the same amount as a rise in tariff by 11 percentage points. Therefore, the collateral damage in terms of foregone trade is sizable.